Volume 6A: Turbomachinery 2013
DOI: 10.1115/gt2013-94566
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pulsed Blowing on the Boundary Layer of a Highly Loaded Low Pressure Turbine Blade

Abstract: The performance of the low pressure turbine (LPT) can vary appreciably, because this component operates under a wide range of Reynolds numbers. At higher Reynolds numbers, mid and aft loaded profiles have the advantage that transition of suction side boundary layer happens further downstream than at front loaded profiles, resulting in lower profile loss. At lower Reynolds numbers, aft loading of the blade can mean that if a suction side separation exists, it may remain open up to the trailing edge. This is esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The suction side flow is imposed on a flat plate in 1:1 scale of the surface length. With matching in-and outlet conditions and without actuation, an excellent correspondence with former studies is shown, compare [9]. The Mach number distribution within the area of interest (white shaded) is shown in Fig.…”
Section: Validation Of the Experimental Testbed And Oscillator Integrsupporting
confidence: 80%
See 4 more Smart Citations
“…The suction side flow is imposed on a flat plate in 1:1 scale of the surface length. With matching in-and outlet conditions and without actuation, an excellent correspondence with former studies is shown, compare [9]. The Mach number distribution within the area of interest (white shaded) is shown in Fig.…”
Section: Validation Of the Experimental Testbed And Oscillator Integrsupporting
confidence: 80%
“…1 left). This design, which has a direct dependency between mass flow rate and frequency, was already used in former studies (see [2,9,13,14]. In contrast to the former applications, the pulsed blowing at the outlet of the feedback oscillator (master) is not directly used for flow control, but for frequency tuning of the oscillator without feedback loops (slave) through the control ports ( Fig.…”
Section: Actuator-coupled Fluidic Oscillatormentioning
confidence: 99%
See 3 more Smart Citations